The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1161/circulationaha.118.038891
|View full text |Cite
|
Sign up to set email alerts
|

Orai1 Channel Inhibition Preserves Left Ventricular Systolic Function and Normal Ca 2+ Handling After Pressure Overload

Abstract: Background: Orai1 is a critical ion channel subunit, best recognized as a mediator of store-operated Ca 2+ entry (SOCE) in nonexcitable cells. SOCE has recently emerged as a key contributor of cardiac hypertrophy and heart failure but the relevance of Orai1 is still unclear. Methods: To test the role of these Orai1 channels in the cardiac pathophysiology, a transgenic mouse was gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 50 publications
3
53
1
1
Order By: Relevance
“…Furthermore, it has been shown that the STIM1/Orai1 complexes were enriched at N-cadherin-rich IDs sites over Cx43-rich sites in adult mice cardiomyocytes (Bonilla et al, 2019). We also noted occasional nuclear Orai1 labeling in isolated mice cardiomyocytes (Bartoli et al, 2020). Indeed, the location of Orai1/STIM1 complex in the nucleoplasm has been reported by other authors as well (Lee et al, 2018), suggesting Orai1 involvement in nucleoplasmic Ca 2+ regulation.…”
Section: Physiological Role Of Orai1 In the Heart Expression And Cellsupporting
confidence: 86%
See 3 more Smart Citations
“…Furthermore, it has been shown that the STIM1/Orai1 complexes were enriched at N-cadherin-rich IDs sites over Cx43-rich sites in adult mice cardiomyocytes (Bonilla et al, 2019). We also noted occasional nuclear Orai1 labeling in isolated mice cardiomyocytes (Bartoli et al, 2020). Indeed, the location of Orai1/STIM1 complex in the nucleoplasm has been reported by other authors as well (Lee et al, 2018), suggesting Orai1 involvement in nucleoplasmic Ca 2+ regulation.…”
Section: Physiological Role Of Orai1 In the Heart Expression And Cellsupporting
confidence: 86%
“…In contrast, heterozygous global Orai1-deficient mice did not present alteration of heart structure and function (Horton et al, 2014). Likewise, we have reported that cardiomyocytespecific dn-Orai1 R91W transgenic mice displayed normal cardiac electromechanical function and ECC despite reduced Orai1dependent SOCE (Bartoli et al, 2020), as recently confirmed in cardiomyocyte-specific and temporally inducible Orai1 knockout (KO) mouse line (Segin et al, 2020). Although in the later study, this was associated with reduced body weight and a downregulation of Orai3, STIM2, and store-operated Ca 2+ entry-associated regulatory factor (SARAF) transcript expression, those results suggested that Orai1 is not instrumental for the ECC and cardiac function at rest.…”
Section: Orai1 Functionmentioning
confidence: 69%
See 2 more Smart Citations
“…Consistent with the literature [ 8 ], our recent studies have demonstrated that Ca 2+ entry is a crucial signal that regulates the pro-fibrotic activity of human cardiac fibroblasts [ 9 , 10 ]. Among the various types of Ca 2+ entry through ion channels in the plasma membrane, the dysfunction of store-operated Ca 2+ entry has recently been found to be the key contributor to heart failure [ 11 , 12 , 13 , 14 ]. Cardiac fibroblasts isolated from patients with heart failure have been reported to possess an enhanced ability to synthesize collagen, which is related to the increase in Ca 2+ entry via elevation in store-operated Ca 2+ entry and the expression level of calcium release-activated calcium channel protein 1 (Orai1) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%